2021
DOI: 10.18632/aging.203624
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ionizing radiation disrupts normal epigenetic aging in Japanese medaka

Abstract: Alterations to the epigenome are a hallmark of biological aging and age-dependent patterning of the DNA methylome (“epigenetic aging”) can be modeled to produce epigenetic age predictors. Rates of epigenetic aging vary amongst individuals and correlate to the onset of age-related disease and all-cause mortality. Yet, the origins of epigenetic-to-chronological age discordance are not empirically resolved. Here, we investigate the relationship between aging, DNA methylation, and environmental exposures in Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 67 publications
(90 reference statements)
1
12
0
Order By: Relevance
“…Using medaka (Oryzias latipes) between 2 and 12 months of age and RRBS (Bertucci et al, 2021) built an epigenetic clock using liver samples. Furthermore, they showed that exposure to ionizing radiation during early development caused epigenetic age acceleration.…”
Section: Piscine Epigenetic Clocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Using medaka (Oryzias latipes) between 2 and 12 months of age and RRBS (Bertucci et al, 2021) built an epigenetic clock using liver samples. Furthermore, they showed that exposure to ionizing radiation during early development caused epigenetic age acceleration.…”
Section: Piscine Epigenetic Clocksmentioning
confidence: 99%
“…Furthermore, they showed that exposure to ionizing radiation during early development caused epigenetic age acceleration. This study is also important because it sets the basis to further explore aging-by-environment interactions (Bertucci et al, 2021). More recently, Weber et al (2022) developed epigenetic clocks for two species present in the Gulf of Mexico, the Northern red snapper (Lutjanus campechanus) and the Red grouper (Epinephelus morio).…”
Section: Piscine Epigenetic Clocksmentioning
confidence: 99%
“…Following the generation of our elastic net epigenetic clocks, we performed BLAST searches of 400 bp regions centered around each clock cytosine and used GenomicRanges to determine the genomic contexts for these sites (genes and CpG islands, shores, shelves, or open seas). Bertucci et al (2021) demonstrated that epigenetic clocks constructed using elastic net approaches on small sample sizes may be overfit, and linear models constructed using cytosines for which the relationship between methylation status and age is greatest…”
Section: Elastic Net Clocksmentioning
confidence: 99%
“…These features have led biomedical fields to turn to DNAm‐based biomarkers to gain insight into biological ageing (Horvath, 2013 ; Horvath & Raj, 2018 ), contaminant exposure (Cardenas et al, 2017 ; Green et al, 2016 ; Gruzieva et al, 2017 ; Joubert et al, 2016 ), and the developmental origins of adult health and disease (Felix & Cecil, 2019 ; Heijmans et al, 2008 ). More recently, the ecological sciences have followed suit, harnessing the potential of the DNA methylome to understand life‐history variation (Anderson et al, 2021 ; Cayuela et al, 2021 ; de Paoli‐Iseppi et al, 2017 ; Lindner et al, 2021 ; Parrott & Bertucci, 2019 ), organismal health (Crossman et al, 2021 ; Hu et al, 2018 ; Lea et al, 2016 ), exposure to environmental stressors (Bertucci et al, 2021 ; Guillette et al, 2016 ; Liew et al, 2018 ; Mäkinen et al, 2022 ; Parrott, Bowden, et al, 2014 ) and developmental plasticity (Laubach et al, 2019 ; Navarro‐Martín et al, 2011 ; Parrott, Kohno, et al, 2014 ; von Holdt et al, 2021 ). Collectively, these studies indicate that DNAm patterns at discrete loci in nonlethally sampled tissues (e.g., blood) provide insight into fundamental aspects of an individual’s biology, health status and past environmental experience that would otherwise be nearly impossible to measure.…”
Section: Introductionmentioning
confidence: 99%